The Role of Private Environmental Governance in Climate Adaptation - Vandenbergh, Michael P.; Johnson, Bruce M. (Frontiers in Climate, 2021)
This Article examines the role of private environmental governance (PEG) in climate change adaptation. PEG occurs when private organizations perform traditionally governmental functions such as providing public goods and reducing negative externalities. PEG initiatives that target climate change mitigation have expanded rapidly in the last decade and have been the subject of research in multiple fields, but PEG initiatives that target climate change adaptation have received less attention. As a first step, the Article develops a definition of private governance regarding climate adaption. It then provides examples of several types of PEG adaptation initiatives, and it concludes by identifying research gaps.